2008
DOI: 10.1002/art.23267
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune disease in individuals and close family members and susceptibility to non‐Hodgkin's lymphoma

Abstract: Objective. Rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and Sjögren's syndrome have been consistently associated with an increased risk of non-Hodgkin's lymphoma (NHL). This study was initiated to evaluate the risks of NHL associated with a personal or family history of a wide range of autoimmune diseases.Methods ). An increased risk of NHL was found for a personal history of 5 nonsystemic autoimmune conditions (autoimmune hemolytic anemia, Hashimoto thyroiditis, Crohn's disease, psoriasis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
106
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 44 publications
14
106
2
2
Order By: Relevance
“…We found a personal history of systemic autoimmune conditions to be significantly associated with a 2.6-fold increased risk of developing NHL. 51 The risks for specific autoimmune conditions varied; however, a significant increased risk was observed for RA, Sjögren's syndrome, SLE, and systemic sclerosis. Furthermore, several other autoimmune conditions were also associated with an increased risk of NHL, both conditions with organ involvement (Hashimoto's thyroiditis, discoid lupus erythematosus, polyarteritis nodosa) and in autoimmune diseases without detectable autoantibodies (Crohn's disease, psoriasis, and sarcoidosis).…”
Section: Lymphomamentioning
confidence: 99%
“…We found a personal history of systemic autoimmune conditions to be significantly associated with a 2.6-fold increased risk of developing NHL. 51 The risks for specific autoimmune conditions varied; however, a significant increased risk was observed for RA, Sjögren's syndrome, SLE, and systemic sclerosis. Furthermore, several other autoimmune conditions were also associated with an increased risk of NHL, both conditions with organ involvement (Hashimoto's thyroiditis, discoid lupus erythematosus, polyarteritis nodosa) and in autoimmune diseases without detectable autoantibodies (Crohn's disease, psoriasis, and sarcoidosis).…”
Section: Lymphomamentioning
confidence: 99%
“…This association was first proposed in 1953 (ZATUCHNI et al, 1953) and successively several epidemiological studies have been performed to explore this risk (Chatterjee et al, 2005, Hill et al, 2003, Duncan & Winkelmann, 1979. A number of sporadic case reports have underlined the association between SSc and NHL, particularly with aggressive B-cell subtypes (Arnaud et al, 2006, Derk et al, 2004, Haviv et al, 1997 and some authors observed an increased risk of NHL among SSc patients, primarily within the first year after the onset of disease, but not beyond 4 years of follow up (Landgren et al, 2006, Mellemkjaer et al, 2008, Rosenthal et al, 1993. Conversely, other studies failed to demonstrate a consistent association between SSc and lymphomas (Chatterjee et al, 2005, Rosenthal et al, 1995, Roumm & Medsger, 1985.…”
Section: Systemic Sclerosismentioning
confidence: 97%
“…A statistically significant increase in risk of HL among patients with a family history of sarcoidosis or ulcerative colitis has been reported, but no association with a family history of other autoimmune conditions has been demonstrated (Landgren et al, 2006). Finally, an association between the risk of lymphoma development and a family history of a wide range of autoimmune diseases has not been detected in a population-based case-control study on 24,728 NHL patients (Mellemkjaer et al, 2008). Likewise, an increased risk of lymphoma occurrence among the first-degree relatives of RA patients has not been proven (Ekstrom et al, 2003).…”
Section: Genetic Factorsmentioning
confidence: 98%
“…A Scandinavian case-control study revealed an increased risk of HL associated with a family history of sarcoidosis and ulcerative colitis (10). A third family study also found that a family history of systemic autoimmune disease (autoimmune hemolytic anemia, Hashimoto thyroiditis, CD, psoriasis, and sarcoidosis) was modestly associated with NHL, although this association was not statistically significant (33). These studies suggest that there are disease-specific predispositions to cancer in families with autoimmune diseases, although the effect size is small.…”
Section: Anti-tnf Therapy and Mechanisms Of Carcinogenesis In Autoimmmentioning
confidence: 99%